Assessment of water availability using indicators: a case study in a transboundary basin - Oñate-Valdivieso, Fernando; Cuenca Torres, Ximena (European Public & Social Innovation Review, 2024)
Introduction: The continued growth of populations and economies has increased the demand for water. The situation is especially complicated in transboundary river basins where the availability of freshwater is increasingly limited, despite the implementation of policies, plans and legislation, aimed at the management and use of the vital liquid. For this reason, the purpose of this research is to evaluate the availability of water resources through the application of indicators. Methodology: Meteorological information was collected, which was processed by applying 3 indices to determine the availability and quality of water in the Catamayo – Chira Transfrontier Basin. Results: The sectoral demand for water was calculated for the Ecuadorian part, determining the Net Water Supply. aridity Water Use and water quality were determined. Discussions: 72% of the total area has a lower requirement for water resources to cover the needs of the vegetation. 63.11% of the basin has acceptable water quality, which indicates that it does not present major contamination that could affect human well-being. Conclusions: The basin presents acceptable conditions of water availability and quality, although an increase in sectoral demands could affect these conditions in the medium term.